2004
DOI: 10.1097/00004872-200401000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin G is associated with atheroma formation in human carotid artery

Abstract: All components required for angiotensin II formation are expressed locally in the arterial wall, where, in the absence of renin, cathepsin G could be a major angiotensin-generating enzyme. Overexpression of ACE and cathepsin G may lead to angiotensin II overproduction and contribute, with decreased number of differentiated smooth muscle cells, to the lower amount of AT1 receptor in atheroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
0
26
2
3
Order By: Relevance
“…Several clinical trials have demonstrated the benefits of AII blockade using anti-hypertensive drugs in reducing acute cardiovascular events, independent of blood pressure reduction [20][21][22] . There are at least 2 receptors for AII present in atheroma, angiotensin receptor type 1 (ATR1) 23) and 2 (ATR2) 24) . Signalling via both receptors has been reported to regulate MMP expression with most studies suggesting ATR1 mediates MMP up-regulation 18) .…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have demonstrated the benefits of AII blockade using anti-hypertensive drugs in reducing acute cardiovascular events, independent of blood pressure reduction [20][21][22] . There are at least 2 receptors for AII present in atheroma, angiotensin receptor type 1 (ATR1) 23) and 2 (ATR2) 24) . Signalling via both receptors has been reported to regulate MMP expression with most studies suggesting ATR1 mediates MMP up-regulation 18) .…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with previous studies showing the expression of angiotensinogen in several arterial beds. [10][11][12][13] Because it is difficult to acquire normal human arterial tissue, we compared the results obtained from atheroma lesions (ATH) to nearby macroscopically intact arterial tissue (MIT). 2 In addition, the importance of using paired ATH and MIT samples from the same patients is that it reduces clinical and demographic variabilities among individuals and increases the statistical power of differential gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we can assume the possibility of formation of angiotensin II from angiotensinogen with cathepsin G participation at the CoCl 2 action which contributes to the development of hypertensive changes. Overexpression of cathepsin G also may lead to decreased number of differentiated smooth muscle cells, to the lower amount of angiotensin 1 receptor in atheroma [34]. Cathepsin G activation in heart can result in myocyte necrosis and increased fibrosis [15].…”
Section: Discussionmentioning
confidence: 99%